Investigating serum iodine nutritional levels and their correlation with thyroid function in adult patients with Graves’ hyperthyroidism at different treatment stages - Wang, Lilan; Ru, Zixuan; Gao, Shengnan; Lv, Na; Li, Kerou; Qiao, Hong (Frontiers in Endocrinology, 2025)
ObjectiveInvestigate the thyroid function and thyroid autoantibodies in adult Graves’ disease (GD) patients at different treatment stages and healthy adults with serum iodine concentration (SIC), and analyze the relationship between SIC and thyroid function as well as thyroid autoantibodies.MethodGD-induced hyperthyroid patients and healthy normal controls will be recruited from the Endocrinology Clinic. Peripheral venous blood samples will be collected, and the SIC content will be determined by the arsenic cerium catalytic spectrophotometry method. Thyroid function indicators will be detected by electrochemical immunoassay analysis, the Pearson/Spearman correlation analysis will be used to analyze the correlation between SIC and thyroid function indicators.ResultsA total of 510 participants were included, of which 80 were healthy adults and 430 had GD. The SIC levels were 63.78 ± 18.92μg/L and 74.09 ± 29.85μg/L. There was a significant difference in SIC levels (100.15 ± 40.25μg/L vs 65.74 ± 19.37μg/L, P < 0.05). In terms of iodine deficiency degree (<45μg/L), there was no significant difference between the two groups (11.25% vs. 12.50%, P>0.05). Correlation analysis showed that SIC was positively correlated with FT4 and TRAb (r=0.213, r=0.369, P<0.05). In newly diagnosed GD patients, the TPOAb concentration and positivity rate in the low blood iodine group were higher than those in the high blood iodine and appropriate blood iodine groups (P<0.05). The TgAb level in the high blood iodine group was greater than that in the low blood iodine and appropriate blood iodine groups (P<0.05), while the TgAb positivity rate in the low blood iodine group was higher than that in the high blood iodine and appropriate blood iodine groups, although there was no significant difference (P>0.05).Conclusions1.The SIC levels in GD patients are higher than those in the healthy control group, and the SIC levels in untreated GD patients are higher than those in treated GD patients.2.There is a potential association between SIC and thyroid function indicators. In newly diagnosed GD patients, SIC shows a positive correlation trend with FT4 and TRAb.3.There are differences in the distribution of patient groups with different iodine contents in the blood, and there are also differences in the levels and positivity rates of TPOAb and TgAb.